Didactic basis of a teacher-engineer trainingin a higher educational institution (Pedagogy of Higher and Secondary Education, 2016)
Pasichna O. V. Didactic basis of a teacher-engineer training in a higher educational institution.The author substantiates the urgency of the issue of teacher-engineers training, who carry out educational activity in professional educational establishments. The content of professional education is revealed.In the article technical-and-technological, psychological and pedagogical components of a teacher-engineer competency are considered. The integrated nature of this profession is highlighted. The components of a teacher-engineer job profile diagram are analyzed.Pecularities of manufacturing characteristics of teacher-engineers are examined. They include requirements for professional knowledge, skills and abilities in a special engineering field, in the field of training and education.The principles (polytechnical, relation between teaching and production labour, modelling of professional activities in teaching and learning process, occupational mobility) and methods (of theoretical instruction and industrial training, vocational training) are described.The author asserts that the use of these principles and methods in the course of teacher-engineers training allows to form their professional competence, improve necessary skills and abilities.
Keywords: vocational training; teacher-engineer; principles of vocational training; methods of theoretical and industrial instruction